(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
For a number of reasons, most libraries do not give serious attention to services for the hearing impaired. Hearing loss is associated with an "invisible disability" in society, as people with hearing loss are not recognized as "deaf" by casual observation and are included in the larger community of healthy people. In addition, people who are hearing impaired from birth or from an early age often have difficulties in reading, and their insufficient reading competence leads to a tendency not to use libraries.